An Analysis of Factors Influencing Pregnant Women’s Understanding of Fe Tablet Benefits at Motoboi Kecil Health Center, Mubago City - Riarisi Fatrichia Hassa; Anik Purwati; Maria Veronika Widiatrilupi (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
The consumption of iron tablets (Fe) among pregnant women in 2013 reached 90.32%, an increase from 82.09% in 2011, showing an improvement of 8.23 percentage points and meeting the target of 90%. Iron tablets are essential for preventing anemia during pregnancy, which can lead to adverse outcomes such as low birth weight and premature birth. This study aims to identify various factors that may influence pregnant women's knowledge about the benefits of iron tablet consumption at the Kotamobagu Small Motoboi Health Center in Mubago City, North Sulawesi. The research employs a cross-sectional descriptive analytical approach, using univariate analysis to examine primary data collected through questionnaires. A sample of 30 pregnant women was selected incidentally for the study. The results indicated a strong correlation between pregnant women's awareness of iron tablets and several demographic and socio-economic factors. Specifically, the chi-squared test revealed significant relationships between pregnant women’s knowledge and their age (p = 0.020), education level (p = 0.020), parity (p = 0.035), and source of information (p = 0.039). These findings suggest that demographic factors such as age and education, along with access to reliable information sources, significantly contribute to the level of knowledge about iron tablet consumption. The study's findings can be used to enhance public health strategies, particularly in increasing awareness among pregnant women about the importance of consuming iron tablets to prevent anemia and improve maternal and fetal health outcomes. Educating pregnant women and providing accessible sources of information are crucial in improving Fe tablet consumption rates and reducing related health risks